Inflammatory low back pain-associated malignancies mimicking spondylarthritis - Albayrak, Fatih; Kisacik, Bunyamin; Gunduz, Ibrahim; Kudas, Ozlem; Koc, Emrah; Zengin, Orhan; Pehlivan, Yavuz (Springer London Ltd, 2024)
Objectives Inflammatory low back pain (IBP) is a typical feature of spondylarthritis (SpA). IBP can be caused by infections, drugs, and different malignancies. Among cancers, hematologic malignancies and solid tumors can cause IBD either paraneoplastically or through metastasis. In this study, we aimed to present the demographic and clinical characteristics of our patients who presented with IBP in the last 10 years and whose final diagnosis was malignancy. Methods Thirty-four patients who presented with inflammatory low back pain in the last 10 years and were diagnosed with malignancy as the final diagnosis were included in the study. Thirty-six patients, diagnosed as axial SpA, with similar age-sex ratio of 1:1 from each center were included as the control group. Results Hematologic malignancies were multiple myeloma, acute leukemia, and lymphoma in descending order. Solid tumors were breast cancer, lung cancer, bone tumors, prostate, colon, embryonal carcinoma, and malignancy of unknown primary. In malignancy-related low back pain, the hematologic/solid ratio was similar (18/16), the interval between symptom and diagnosis was shorter, and biomarkers' results such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and serum lactate dehydrogenase (LDH) levels were significantly higher than the control group. Conclusion Malignancy-related low back pain differs from SpA patients with a more severe clinical picture, higher acute phase reactants levels, and higher LDH values. Malignancies must be kept in mind in the differential diagnosis, and in order to validate our findings, the results of larger case series are needed, especially in terms of causative malignancies.
Keywords: Hematological malignancy; Inflammatory low back pain; Malignancy; Solid tumors; Spondylarthritis